Isolation of amygdalin epimer at high diastereomeric purity and its structural characterization by spectroscopic and Q-TOF LC-MS methods - Sabir, Pshtiwan Raheem; Capan, Irfan; Aysal, Ayhan Ibrahim; Servi, Suleyman (Acg Publications, 2021)
Amygdalin, a cyanogenic glycoside mostly found in the bitter almond kernel, plays an important role in conventional and modern medicine applications. The high diastereomeric purity amygdalin was isolated with chromatographic purification methods and recrystallization. Amygdalin and neoamygdalin were separated chromatographically using the porous graphitic carbon column. Identification and confirmation of each molecule was performed with the ESI Quadrupole Time of Flight system coupled with a reversed phase LC.
Keywords: Amygdalin; neoamygdalin; cyanogenic glycoside; LC-MS Q-TOF; chromatography